2014
DOI: 10.5545/sv-jme.2013.1486
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Wall Thickness Distribution in Simple Thermoforming Moulds

Abstract: Thermoforming is widely used in manufacturing industries to produce large and labour-intensive products. Compared to other manufacturing techniques, thermoforming is an extremely efficient process that is suitable for high-efficiency mass production. In this paper, experimental thermoforming operations were carried out using a lab-scale, sheet-fed thermoformer. Carbon fibre-reinforced PP and unreinforced PS thermoplastic sheets were used in experimental thermoforming operations. The processing parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
11
0
4
Order By: Relevance
“…[2,[7][8][9]12,14,21]. To obtain commercially acceptable trays, processing parameters for each material were optimized based on stability and visual criteria of the formed trays.…”
Section: Analysis Of the Thickness After Thermoformingmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,[7][8][9]12,14,21]. To obtain commercially acceptable trays, processing parameters for each material were optimized based on stability and visual criteria of the formed trays.…”
Section: Analysis Of the Thickness After Thermoformingmentioning
confidence: 99%
“…However, various studies have shown that the OTR of the sheet material cannot easily be extrapolated to thermoformed packaging [4][5][6]. One of the reasons might be a poor control of the material thickness distribution in the walls, the corners, and/or the bottom, which is a major drawback of thermoforming [7][8][9]. On the other hand, the effect of physical thinning on the OTR can be partially neutralized by reorientation, closer chain packaging, and restriction of chain mobility of polymer chains in the amorphous zones during deep drawing and stretching of the material [10].…”
Section: Introductionmentioning
confidence: 99%
“…• The parameters of heating influence all types of geometrical and dimensional errors in a more significant way, considering all their different levels. • In addition to mold characteristics [15], [36] the parameters of mold can influence geometric errors; • The interaction of two factors can influence the deviations of the product by reducing the value of dimensional errors, but a significant increase of geometric errors can occur; • The manufacturing parameters interact simultaneously with the errors in a non-linear and non-proportional model;…”
Section: Errors (Mm)mentioning
confidence: 99%
“…It was found that the friction coefficient of the sheet varying with temperature greatly influences the thickness distribution. Erdogan and Eksi [8] investigated the effect of circular and rectangular clamping tools to the thickness distribution. The side areas and bottom areas of the thermoformed products are significantly affected by the geometry of the clamping tool.…”
Section: Introductionmentioning
confidence: 99%